Arterial Hypertension in Adolescents from Moa. Prevalence and Clinical Characterization - Alexander Torres Molina (Revista Finlay)
Foundation: high blood pressure is a disease of multifactorial origin related to genetic and environmental factors, which has experienced a notable increase in its prevalence in recent years. It is a silent cause of morbidity and target organ damage in adolescents. Early detection of this condition is important as a risk marker for hypertension in adulthood. Objective: determine the prevalence and characterize arterial hypertension in adolescents 15-19 years of age. Methods: a cross-sectional study was carried out in the period from September to December 2022. The universe consisted of 1,561 adolescents aged 15-19 years, the sample being 1,444 (92.50 %). The sampling was systematic probabilistic. The variables analyzed were: age, sex, skin color, prehypertension and arterial hypertension (systolic, diastolic and systodiastolic) and severity of hypertension. The statisticians were analyzed: frequency, percentage and prevalence. Results: 8.21 % were diagnosed with prehypertension and 39 (7.44 %, apparent prevalence) with hypertension. 7.69 % of hypertensive patients had elevated diastolic blood pressure, 35.90 % had elevated systolic blood pressure, and 56.41 % both. 89.74 % of hypertensive patients were in stage 1 and 10.26 % in stage 2. Conclusions: the prevalence of arterial hypertension in the adolescents included in the research was higher than that reported in Cuba. The highest percentage of patients with prehypertension and high blood pressure was seen in people over 19 years of age, men, and black skin color.